Theodor Storm's Novellen Essays on Literary Technique - McCormick, E. Allen (UNC Studies in the Germanic Languages and Literatures, 1964)
These six essays elucidate some of the more significant aspects of Storm's literary technique. The treatments of some of Storm's "Novellen", including "Am Kamin", "Aquis Submersus" and two versions of "Immensee", show how Storm used structure, symbolism, elements of tragedy and other narrative devices in his prodigious body of works of German Realism.